The epidemiological investigation of bed bugs, Cimex lectularius in Jeddah governorate, Saudi Arabia - Khan, Samar A.; Mahyoub, Jazem A.; Al-Ghamdi, Khalid M.; Gharsan, Fatehia N.; Elhassan, Somia A. Mohammed; Alghamdi, Tariq S. (International Journal of Research in Dermatology, 2020)
Background: Bed bugs are small insects that feed on animal blood at all stages of their life cycle, with the most common species, Cimex lectularius, preferring to feed on human blood. In recent years, it has reappeared in many countries around the world. Methods: Samples of bed bugs were collected from Jeddah governorate neighbourhoods from 4th December, 2018, to 1st May, 2019, to determine the infected neighbourhoods and the degree of insect infestation. The study was conducted by random selection of individuals in the Jeddah community; data were collected through the completion of 1000 questionnaires, which were then statistically analysed. Results: The current study monitored the presence of bed bugs in many neighbourhoods of Jeddah governorate; their presence percentage varied according to the different neighbourhoods, and they were arranged in descending order according to the percentage of their presence as follows: Al-Safa >Bani-Malik >Al-Sherafiya >Al Jamaa >Al Nuzula. The prevalence of bed bugs related to the population density, random neighbourhoods, low level of hygiene in the neighbourhood, and moving from one residence to another. 98% of the residents of Jeddah in the sample agreed that bed bugs were a disturbing pest and an environmental problem which needs to be researched and studied to reach the best ways to control it, as 99.6% of them agreed the necessity of including bed bugs in the list of disturbing pests and vectors of diseases that must be controlled by the concerned authorities in Jeddah governorate. Conclusions: The necessity of including bed bugs as one of the pests that need to be considered and must be controlled by the relevant authorities.